2014
DOI: 10.1109/tbme.2014.2311118
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Renal Perfusion Signals From Laser Speckle Imaging Into Clusters With Phase Synchronized Dynamics

Abstract: Renal perfusion signals contain dynamics arising from the renal autoregulation feedback mechanisms as the contraction and dilation of vessels alter flow patterns. We can capture the time-varying dynamics at points across the renal surface using laser speckle imaging. We segment an imaged area of the renal cortex into clusters with phase synchronized dynamics. Our approach first uses phase coherence with a surrogate data derived threshold to identify synchronized pixel pairs. Non-negative matrix factorization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 34 publications
3
22
1
Order By: Relevance
“…Previous studies showed that record lengths of 30 -50 cycles (300 s) are required to probe MR synchronization (36), and pilot studies showed the same 30-to 50-cycle (1,500 s) requirement for probing TGF synchronization. BP, RBF, and LSCI signals were acquired during spontaneous BP fluctuation before and after injection of L-NAME (Sigma, 10 mg/kg iv) in 10 rats.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that record lengths of 30 -50 cycles (300 s) are required to probe MR synchronization (36), and pilot studies showed the same 30-to 50-cycle (1,500 s) requirement for probing TGF synchronization. BP, RBF, and LSCI signals were acquired during spontaneous BP fluctuation before and after injection of L-NAME (Sigma, 10 mg/kg iv) in 10 rats.…”
Section: Methodsmentioning
confidence: 99%
“…Synchronization of oscillators can be addressed by assessment of phase locking or of frequency entrainment (31); however, phase locking is the standard definition of synchronization (1,31). Thus determination of synchronization on the surface of the kidney used methods described in detail elsewhere (36) that are based on assessment of the stability in time of phase relationships among pixels. Briefly, each image was filtered with a Gaussian spatial filter (8-pixel width) and then down-sampled by a factor of 4, yielding a 27 ϫ 37-pixel image for each frame with average pixel size of 135 ϫ 135 m (36, 37).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations